Variabel - Variabel yang Berpengaruh Terhadap Harga Pasar Saham Pada Perusahaan Kelapa Sawit yang Terdaftar di Bursa Efek Indonesia Tahun 2015 – 2020 - Yulius Triadi Limandra; Agus Rahman Alamsyah; Ike Kusdiyah Rachmawati (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2023)
The number of capital market investors in Indonesia is very minimal, as of July 2022 there were 8.88 million accounts consisting of Stock investors, with 42% of them being stock investors and 60.29% dominated by millennials. Fundamental factors are represented by liquidity ratios, solvency ratios, activity ratios, and performance ratios. The study was conducted using a quantitative approach, with a population of 24 oil palm plantation companies listed on the Indonesia Stock Exchange. The research sample consisted of 5 oil palm plantation companies selected using the purposive sampling method. The statistical method used in this study is multiple regression analysis. The results of this study indicate 1) the liquidity ratio expressed by Working Capital to Total Asset Ratio and the Quick Asset Ratio has no significant effect on stock market prices, 2) the solvency ratio expressed by the Debt to Asset Ratio has a significant effect on stock market prices, 3) the activity ratio which is expressed by Total Assets Turn Over has no significant effect on the Stock Market Price, and 4) Performance Ratios expressed by Earning Per Share, have a significant effect on Market price